Research on the performance of the PPP-AR technique under different FCB product services - Karlitepe, Furkan; Erdogan, Bahattin (TAYLOR & FRANCIS LTD, 2024)
Researchers and manufacturers use the Precise Point Positioning (PPP) technique. After the phase biases of the satellites are resolved from GNSS networks, they are broadcast to users as Fractional Cycle Bias (FCB). In this study, FCB products provided by WUHAN, CODE, CNES and JAXA services were downloaded and PPP Ambiguity Resolution solutions were realised by Net_Diff software. For ten days in 2022, 24-hour observations were collected from 40 International GNSS Service stations. As a result, it has been observed that WUHAN and CODE services provided the & PLUSMN;1 cm or & PLUSMN;5 cm accuracy level by converging in short-term observations.
Keywords: PPP-AR; Convergence time; Fractional cycle bias; GNSS; Integer ambiguity; INTEGER AMBIGUITY RESOLUTION; PRECISE; Engineering; Geology; Remote Sensing